Please, I need to express the following equations to get the value of M_tot. I write the equations and successfully ran the code but the result is not what I had anticipated.
Please help, I need to express the following equations to get the value of M_tot. I have already written the relevant equations and successfully ran the code, but the result is not what I had anticipated. Would you kindly examine the following code and compare it with the equations for the system?
Sf = 0.01;
Mo = 4*pi*10^-7 ;
Mr = 3200;
Fr= 85000;
w = 2*pi*Fr;
t_TX = 0.01;
t_RX = 0.02;
rs = 0.00006;
r_TX = 17.32*1.58*rs;
r_RX = 17.32*1.58*rs;
R_TX = 0.045;
R_RX = 0.045;
h = 0.3;
d_TX = 0.01;
d_RX = 0.01;
N_TX = 10;
N_RX = 10;
s = 0.005;
Func = 0;
M_fer = 0;
M_air = 0;
syms k
syms x
i
f1 = sqrt ((k^2)+i*(w*Mo*Mr*Sf));
f2 = (Mr-(f1/k))/(Mr+(f1/k));
f3_TX = f2*(1-exp(-2*f1*t_TX)) / (1-((f2)^2)*(exp(-2*f1*t_TX)));
f3_RX = f2*(1-exp(-2*f1*t_RX)) / (1-((f2)^2)*(exp(-2*f1*t_RX)));
f4 = ((f3_TX)*exp(-k*((2*r_TX) + r_RX + h + d_RX)) + (f3_RX * exp(-k*((2*r_RX) + r_TX + h + d_TX))))/(1 – (f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX))));
f5 = (2 * f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX)) * cosh(k*(r_TX + r_RX + h))) / (1 – (f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX))));
for i = 1:N_TX
R_TXn = R_TX + (N_TX – 1)*(s+ 2*r_TX);
for j = 1:N_RX
R_RXn = R_RX + (N_RX – 1)*(s+ 2*r_RX);
Func = @(k) Mo.*pi.*R_TXn.*R_RXn.* ( besselj(1,(R_TXn.*k)) .* besselj(1,(R_RXn.*k)) .* (f4 + f5));
M_fer = vpaintegral(Func(k),k,0,inf);
f = sqrt ((4.*R_TXn.*R_RXn)./ ((r_TX + r_RX + h)^2 +(R_TXn + R_RXn)^2) );
[K_f,E_f] = ellipke(f);
M_air = Mo.*sqrt(R_TXn.*R_RXn).*(2./f).*((1-0.5.*(f^2)).*(K_f) – E_f) ;
end
end
M_tot = M_fer + M_airPlease help, I need to express the following equations to get the value of M_tot. I have already written the relevant equations and successfully ran the code, but the result is not what I had anticipated. Would you kindly examine the following code and compare it with the equations for the system?
Sf = 0.01;
Mo = 4*pi*10^-7 ;
Mr = 3200;
Fr= 85000;
w = 2*pi*Fr;
t_TX = 0.01;
t_RX = 0.02;
rs = 0.00006;
r_TX = 17.32*1.58*rs;
r_RX = 17.32*1.58*rs;
R_TX = 0.045;
R_RX = 0.045;
h = 0.3;
d_TX = 0.01;
d_RX = 0.01;
N_TX = 10;
N_RX = 10;
s = 0.005;
Func = 0;
M_fer = 0;
M_air = 0;
syms k
syms x
i
f1 = sqrt ((k^2)+i*(w*Mo*Mr*Sf));
f2 = (Mr-(f1/k))/(Mr+(f1/k));
f3_TX = f2*(1-exp(-2*f1*t_TX)) / (1-((f2)^2)*(exp(-2*f1*t_TX)));
f3_RX = f2*(1-exp(-2*f1*t_RX)) / (1-((f2)^2)*(exp(-2*f1*t_RX)));
f4 = ((f3_TX)*exp(-k*((2*r_TX) + r_RX + h + d_RX)) + (f3_RX * exp(-k*((2*r_RX) + r_TX + h + d_TX))))/(1 – (f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX))));
f5 = (2 * f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX)) * cosh(k*(r_TX + r_RX + h))) / (1 – (f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX))));
for i = 1:N_TX
R_TXn = R_TX + (N_TX – 1)*(s+ 2*r_TX);
for j = 1:N_RX
R_RXn = R_RX + (N_RX – 1)*(s+ 2*r_RX);
Func = @(k) Mo.*pi.*R_TXn.*R_RXn.* ( besselj(1,(R_TXn.*k)) .* besselj(1,(R_RXn.*k)) .* (f4 + f5));
M_fer = vpaintegral(Func(k),k,0,inf);
f = sqrt ((4.*R_TXn.*R_RXn)./ ((r_TX + r_RX + h)^2 +(R_TXn + R_RXn)^2) );
[K_f,E_f] = ellipke(f);
M_air = Mo.*sqrt(R_TXn.*R_RXn).*(2./f).*((1-0.5.*(f^2)).*(K_f) – E_f) ;
end
end
M_tot = M_fer + M_air Please help, I need to express the following equations to get the value of M_tot. I have already written the relevant equations and successfully ran the code, but the result is not what I had anticipated. Would you kindly examine the following code and compare it with the equations for the system?
Sf = 0.01;
Mo = 4*pi*10^-7 ;
Mr = 3200;
Fr= 85000;
w = 2*pi*Fr;
t_TX = 0.01;
t_RX = 0.02;
rs = 0.00006;
r_TX = 17.32*1.58*rs;
r_RX = 17.32*1.58*rs;
R_TX = 0.045;
R_RX = 0.045;
h = 0.3;
d_TX = 0.01;
d_RX = 0.01;
N_TX = 10;
N_RX = 10;
s = 0.005;
Func = 0;
M_fer = 0;
M_air = 0;
syms k
syms x
i
f1 = sqrt ((k^2)+i*(w*Mo*Mr*Sf));
f2 = (Mr-(f1/k))/(Mr+(f1/k));
f3_TX = f2*(1-exp(-2*f1*t_TX)) / (1-((f2)^2)*(exp(-2*f1*t_TX)));
f3_RX = f2*(1-exp(-2*f1*t_RX)) / (1-((f2)^2)*(exp(-2*f1*t_RX)));
f4 = ((f3_TX)*exp(-k*((2*r_TX) + r_RX + h + d_RX)) + (f3_RX * exp(-k*((2*r_RX) + r_TX + h + d_TX))))/(1 – (f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX))));
f5 = (2 * f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX)) * cosh(k*(r_TX + r_RX + h))) / (1 – (f3_TX * f3_RX * exp(-k*((2*r_TX) + (2*r_RX) + h + d_TX + d_RX))));
for i = 1:N_TX
R_TXn = R_TX + (N_TX – 1)*(s+ 2*r_TX);
for j = 1:N_RX
R_RXn = R_RX + (N_RX – 1)*(s+ 2*r_RX);
Func = @(k) Mo.*pi.*R_TXn.*R_RXn.* ( besselj(1,(R_TXn.*k)) .* besselj(1,(R_RXn.*k)) .* (f4 + f5));
M_fer = vpaintegral(Func(k),k,0,inf);
f = sqrt ((4.*R_TXn.*R_RXn)./ ((r_TX + r_RX + h)^2 +(R_TXn + R_RXn)^2) );
[K_f,E_f] = ellipke(f);
M_air = Mo.*sqrt(R_TXn.*R_RXn).*(2./f).*((1-0.5.*(f^2)).*(K_f) – E_f) ;
end
end
M_tot = M_fer + M_air mutual_inductance MATLAB Answers — New Questions